EVALUASI POLA TERAPI PENGOBATAN PENYAKIT-PENYAKIT PENYERTA (KOMORBID) PADA PASIEN HIV/AIDS DI RUANG RAWAT INAP RUMAH SAKIT UMUM IMELDA PEKERJA INDONESIA MEDAN - Gultom, Roby (Universitas Imelda Medan, 2022)
Comorbid diseases can be found in HIV/AIDS pateients. Comorbid are comorbid diseases that are not related to the diagnosis of the main disease or the patients condition. The purpose of this study was todetermine the pattern of therapy comorbid diseases (comorbid) in HIV/AIDS patients in the inpatient room at Rumah Sakit Umum Imelda Pekerja Indonesia Medan. The sample of this study amounted to 34 people. This type of research is a descriptive observation study where the date are taken retrospectively and analyzed by descriptive statistical methods. The result showed that majority of patients in Rumah Sakit Umum Imelda Pekerja Indonesia Medan is men as many 27 people (79,4%). The most common comorbid diseases foun in HIV/AIDS patients is hyponatremiaas many 20 people (25%), hypokalemia as many 12 people (15%), and dyspepsia as many as 9 people (11,25%). The most common comorbid treatment patterns given to HIV/AIDS patients are antibiotic abd analgesic. Where the antibiotic is ceftriaxone (52.9%) and the analgesic is ketorolac (61.8%), In addition, there is the provision of diarrhea medicine using Diaform (55.9%), Stomach medicine using Antacids (52.9%), suplements using Channa (44,1%) and sedatives using Alprazolam (52.9%). In addition to treatment therapy, HIV/AIDS patients also recived blood transfusion as many as 5 people.